Acceptability measures for evaluating smoking cessation interventions among individuals with diabetes - Joseph Grech; Ian James Norman; Roberta Sammut (Elsevier, 2024)
Background: The literature indicates that individuals with diabetes do not easily adopt smoking cessation interventions. Given that the success of such interventions depends on patient involvement and attitudes, assessing intervention acceptability, including patient satisfaction and perceived usefulness, is crucial before implementing a smoking cessation intervention. This paper reports the preliminary validation of the satisfaction and perceived usefulness questionnaires for evaluating smoking cessation interventions among individuals with diabetes. Study design: Validity study. Methods: The satisfaction questionnaire contained eight statements while the perceived usefulness questionnaire had fourteen; both rated on a 5-point Likert scale. Content validation involved five tobacco cessation facilitators rating item relevance using a 4-point ordinal rating scale, suggesting improvements. The questionnaires were also translated into Maltese for local use and assessed for translation validity using a similar scale. Unanimous agreement among experts was required for item relevance and equivalence. Thirty-four individuals with type 1 or type 2 diabetes, attending a diabetes-specific smoking cessation intervention, received either the Maltese or English versions of the questionnaires. Internal consistency was measured using Cronbach's alpha. Results: After two rounds of content validation, the experts unanimously agreed on item relevance and conceptual equivalence. Fifteen and sixteen participants completed the Maltese and English versions of the questionnaires, respectively. Both questionnaires' versions were found to have a high internal consistency (>0.8). Conclusions: These findings provide the initial validation of these instruments for assessing the acceptability of smoking cessation interventions among individuals with diabetes. Further validation in different settings using a larger sample is suggested.